2017
DOI: 10.1080/1547691x.2017.1360968
|View full text |Cite
|
Sign up to set email alerts
|

Estimated exposures to perfluorinated compounds in infancy predict attenuated vaccine antibody concentrations at age 5-years

Abstract: Perfluorinated alkylate substances (PFASs) are highly persistent and may cause immunotoxic effects. PFAS-associated attenuated antibody responses to childhood vaccines may be affected by PFAS exposures during infancy, where breastfeeding adds to PFAS exposures. Of 490 members of a Faroese birth cohort, 275 and 349 participated in clinical examinations and provided blood samples at ages 18 months and 5 years. PFAS concentrations were measured at birth and at the clinical examinations. Using information on durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 179 publications
(144 citation statements)
references
References 45 publications
7
135
1
1
Order By: Relevance
“…In the birth cohorts, higher maternal concentrations of PFASs during pregnancy were associated with lower anti-vaccine antibody levels for rubella [58], diphtheria [51] and tetanus [55] in their children at ages 3 to 5 years. No consistent associations were found however between prenatal concentrations of PFASs and vaccine antibody levels for influenza and measles among the children [58].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the birth cohorts, higher maternal concentrations of PFASs during pregnancy were associated with lower anti-vaccine antibody levels for rubella [58], diphtheria [51] and tetanus [55] in their children at ages 3 to 5 years. No consistent associations were found however between prenatal concentrations of PFASs and vaccine antibody levels for influenza and measles among the children [58].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…No consistent associations were found however between prenatal concentrations of PFASs and vaccine antibody levels for influenza and measles among the children [58]. Childhood and infancy exposure to PFASs has also been shown to decrease vaccine antibody levels for diphtheria and tetanus in children aged 5 to 13 years in longitudinal studies from the Faroe Islands [51, 5355]. Finally, cross-sectional measures of PFASs and rubella and mumps titers in adolescents aged 12 to 19 years in NHANES showed lower levels for these antibodies in relation to higher PFAS concentrations [48].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Well-known cohort studies in the Faroe Islands have associated autoantibodies with prenatal and childhood exposure to environmental chemicals such as methylmercury, PCBs, and PFASs in Faroese children (Osuna, Grandjean, Weihe, & El-Fawal, 2014). In contrast, vaccine-elicited antibody responses against diphtheria (Grandjean et al, 2012) and tetanus (Grandjean et al, 2017) were reduced upon prenatal exposure to PCB and PFASs as previously discussed in the immunosuppression section. Evaluated autoantibodies were specific to both neural (neurofilaments, choline acetyltransferase, astrocyte glial fibrillary acidic protein, and myelin basic protein) and nonneural (actin, desmin, and keratin) antigens (Osuna et al, 2014).…”
Section: Autoimmunitymentioning
confidence: 87%
“…However, in a recent study, we modeled serum concentrations during infancy and found that levels at ages 3 and 6 months appeared to be at least as strong predictors of decreased vaccine responses at age 5 years as was the maternal concentrations [17]. The time dependence is difficult to explore in detail due to the complexity of obtaining blood samples from small children.…”
Section: Discussionmentioning
confidence: 99%
“…We prospectively followed birth cohorts in the Faroe Islands and showed that developmental PFAS exposures constitute a major determinant for antibody concentrations directed against tetanus and diphtheria toxoids at ages 5 and 7 years, i.e., after three or four routine vaccinations [16,17]. Our most recent findings suggest that elevated serum-PFAS concentrations in infancy are particularly associated with lower antibody concentrations at age 5 [17]. In contrast, at age 7 years, the postnatal PFAS accumulation seems to play a major role [16].…”
Section: Introductionmentioning
confidence: 99%